Contribution of aerogravity data interpretation to the study of the deep structure of Agadem petroleum block (Niger) - Halidou Amadou, Abdourhamane; El Azzab, Driss; Chaouni, Abdel Ali (Geodesy and Cartography, 2023)
The main information provided by gravity maps is the geographical distribution of density heterogeneities in the subsurface. It is an important tool widely used for the mapping of geological structures, especially in the oil industry. Thus, this study based on the interpretation of aerogravity data has for objective, the qualitative description of the characteristics of the gravity anomalies of the study area, interpretation and mapping of the gravity lineaments as well as their depths, knowing that the lineaments constitute potential structural traps favorable to the accumulation of the hydrocarbons. Methods such as horizontal derivative, upward continuation and Euler deconvolution are used to give a geological signifiance to the different anomalies and to highlight deep structures. Thus, the analysis of the residual anomaly map revealed elongated negative and positive anomaly zones, oriented globally NW-SE, considered respectively as horst and graben zones. Gravity lineaments, considered as normal faults, are mapped using the horizontal gradient method. Finally, the depths of the density contrasts are estimated by the Euler deconvolution calculation using the value “1” as structural index. The depths thus determined are highly variable. The shallowest depths vary between 3000 m and 6000 m, while the deepest depths reach 18000 m.